1984
DOI: 10.1063/1.334308
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of collisionally pumped 3s-3p lasers in the neon isoelectronic sequence

Abstract: Population inversions between the 3p and 3s levels of neonlike ions with atomic numbers Z=14, 18, 22, 26, 32, and 36 have been calculated. The population inversions result from the preferential population of the 3p level by electron collisional excitation from the ground configuration of the ion and occur over a wide range of electron temperature and electron density (from 1017 cm−3 for Si V to 1022 cm−3 for Kr XXVII). For all ions that are studied, the maximum value of the population inversion (N3p/g3p−N3s/g3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 6 publications
5
32
0
Order By: Relevance
“…levels will be negligible compared to collisional depopulations and all level population become independent of electron density and approximately equal (see Figures 1 and 2). The population inversion is largest where electron collisional de-excitation rate for the upper level is comparable to radiative decay for this level [21]. Form our study, it was found that the gain coefficient was very low at (1/4 ionization potential) for all elements, so the results of gain coefficient and reduced population have not been mentioned.…”
Section: Level Populationsmentioning
confidence: 74%
“…levels will be negligible compared to collisional depopulations and all level population become independent of electron density and approximately equal (see Figures 1 and 2). The population inversion is largest where electron collisional de-excitation rate for the upper level is comparable to radiative decay for this level [21]. Form our study, it was found that the gain coefficient was very low at (1/4 ionization potential) for all elements, so the results of gain coefficient and reduced population have not been mentioned.…”
Section: Level Populationsmentioning
confidence: 74%
“…The population inversion was predicted in optically thin Ne-like system [1,4] with only 27 levels of n = 3 and without including the ionization and dielectronic recombination atomic processes. The elaborated inodels which have been recently developed for Ne-like system [2,5,7,8] take into account more excited levels of lasing ions and include some levels of both F-like and Na-like ions.…”
Section: Atomic Processes and Cre Schemementioning
confidence: 99%
“…However, only 27 levels belonging to the configurations 1s 2 2s2 2p6 , 1s2 2s2 2ρ5 3s, 1s2 2s2 2p5 3p, and 1s2 252 2p5 3d of these ions have been taken into account. The ionization and dielectronic recombination processes, neglected in this simulation [1,4], have shown a significant effect on the gain magnitudes [2,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations